1990
DOI: 10.1007/bf02779192
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelial cyst in the pancreas: A case report

Abstract: A case of lymphoepithelial cyst in the pancreas was reported. A 64-year-old man without any specific complaints was found to have a cystic lesion in the anterior portion of the pancreas, as revealed by ultrasonography of the abdomen at an annual medical examination in 1988. This was dissected easily from the pancreas. Histologically, it was diagnosed to be a benign lymphoepithelial cyst in the pancreas. Cysts of this type are rare, and their histogenesis is also not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 2 publications
0
19
1
Order By: Relevance
“…Although elevations of serum CA 19-9 [11] , cyst fluid CA 19-9 [12] and persistence of elevated CA 19-9 postresection [13] have been described in lymphoepithelial cysts, none of our patients had such abnormal levels. Thus, we believe that this marker has no utility in the clinical assessment of these cystic lesions [14] .…”
contrasting
confidence: 69%
“…Although elevations of serum CA 19-9 [11] , cyst fluid CA 19-9 [12] and persistence of elevated CA 19-9 postresection [13] have been described in lymphoepithelial cysts, none of our patients had such abnormal levels. Thus, we believe that this marker has no utility in the clinical assessment of these cystic lesions [14] .…”
contrasting
confidence: 69%
“…All patients have been men and ranged from 36 to 73 years of age, similar to the two patients presented here. Yamamoto et al [6] and Hisaoka et al [4] have previously reported serum CA 19-9 elevations in patients with lymphoepithelial cysts. Similarly, Kaiserling et al [9] reported CEA and CA 19-9 elevations in the serum as well as in cyst fluid.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, there have been only 16 pathologically proven case reports in the English literature, many of them reported in the pathology literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. We report two cases, with emphasis on the computed tomography (CT) and sonographic findings.…”
mentioning
confidence: 88%